Role of MicroRNA-143 in Nerve Injury-Induced Upregulation of Dnmt3a Expression in Primary Sensory Neurons - Xu, Bo; Cao, Jing; Zhang, Jun; Jia, Shushan; Wu, Shaogen; Mo, Kai; Wei, Guihua; Liang, Lingli; Miao, Xuerong; Bekker, Alex; Tao, Yuan-Xiang (Frontiers in Molecular Neuroscience, 2017)
Peripheral nerve injury increased the expression of the DNA methyltransferase 3A (Dnmt3a) mRNA and its encoding Dnmt3a protein in injured dorsal root ganglia (DRG). This increase is considered as an endogenous instigator in neuropathic pain genesis through epigenetic silencing of pain-associated genes (such as Oprm1) in injured DRG. However, how DRG DNMT3a is increased following peripheral nerve injury is still elusive. We reported here that peripheral nerve injury caused by the fifth spinal nerve ligation (SNL) downregulated microRNA (miR)-143 expression in injured DRG. This downregulation was required for SNL-induced DRG Dnmt3a increase as rescuing miR-143 downregulation through microinjection of miR-143 mimics into injured DRG blocked the SNL-induced increase in Dnmt3a and restored the SNL-induced decreases in Oprm1 mRNA and its encoding mu opioid receptor (MOR) in injured DRG, impaired spinal cord central sensitization and neuropathic pain, and improved morphine analgesic effects following SNL. Mimicking SNL-induced DRG miR-143 downregulation through DRG microinjection of miR143 inhibitors in naive rats increased the expression of Dnmt3a and reduced the expression of Oprm1 mRNA and MOR in injected DRG and produced neuropathic pain-like symptoms. These findings suggest that miR-143 is a negative regulator in Dnmt3a expression in the DRG under neuropathic pain conditions and may be a potential target for therapeutic management of neuropathic pain.